KETERKAITAN LAND SURFACE TEMPERATURE DENGAN LANDCOVER DI UNIVERSITAS INDONESIA PADA TAHUN 2013 DAN 2025 - Makarim, Alisha Nisrina (Jurnal Geografi, 2025)
As urbanization continues to grow in the Jabodetabek region, particularly in Depok where the University of Indonesia is located, surface air temperature has increased. This study aims to examine how land cover changes over time influence temperature in this area. Using Landsat 8 OLI/TIRS Collection 2 Tier 1 satellite data, thermal bands (TIRS) were used to extract Land Surface Temperature, while multispectral bands (OLI) were used to generate vegetation indices. Data processing was carried out using Google Earth Engine to obtain LST values for the University of Indonesia. The results show a temperature increase of 4.36°C over 12 years from 2013 to 2025. This rise correlates with land cover transformation driven by infrastructure development in the main campus area. A clear spatial pattern is observed: northern areas exhibit lower temperatures due to dominant vegetation and water bodies, while southern areas show higher temperatures due to built-up areas, asphalt roads, and impervious surfaces. The study concludes that land cover change at the University of Indonesia significantly contributes to the increase in Land Surface Temperature.